An Assessment of Character building in light of National Professional Standards of Public Sector Teachers at Primary Level in District Peshawar (British Journal of Multidisciplinary and Advanced Studies, 2022)
The main objective of the study was to assess the teaching practices of the public sector primary school teachers in light of the national professional standards (NPS) approved by the Ministry of Education (MoE) on 23rd February 2009 in collaboration with the financial support of the USAID. The program was named as STEP which stands for strengthening Teacher Education Program. The study was delimited to only 3rd standard, being related to character building. For data collection, a criteria based Rubric was constructed. Data was collected from 360 public sector primary school teachers of District Peshawar. Collected Data, for selected standard, was analyzed through mean score. Findings of the study showed that majority of the teachers didn’t perform as per investigated Standard. So, it was recommended that Education department should chalk out a widespread program for the training and supervision of public sector primary school teachers regarding Character building of students.